Integration of ASEAN Outlook on Indo-Pacific (AOIP) Cooperative Functionalism in the Joko Widodo Era: An Analysis of Indonesia’s Strategic Mechanisms and Regional Impact (2014-2024) - Laode Muhamad Fathun; Alfiyah Nur Rahmalia; Audrey Chairunnisa Imanjaya; Pribadi Sutiono (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2026)
This article examines Indonesia’s implementation of the ASEAN Outlook on the Indo-Pacific (AOIP) during President Joko Widodo’s administration (2014-2024), focusing on the country’s “open-ended mechanism” approach to regional integration. Drawing on functionalist integration theory, we analyze how Indonesia leveraged AOIP’s framework to create flexible cooperation platforms that accommodate diverse interests while building functional integration across maritime cooperation, connectivity, sustainable development, and economic domains. Through examination of diplomatic initiatives, sub-regional programs like BIMP-EAGA, and external partnership frameworks, we assess whether Indonesia’s strategy generated genuine regional integration or merely episodic cooperation. Our findings reveal a mixed outcome: while AOIP achieved moderate success in institutional development and sector-specific interdependence, particularly in maritime and economic domains, it failed to demonstrate functionalist spillover effects or political convergence among member states. The study concludes that Indonesia’s open-ended mechanism represents “integration without supranationalism” a distinctively flexible approach to regionalism that increases interdependence without sovereignty pooling, reflecting both the possibilities and limits of middle power leadership in an era of intensifying great power competition.